Consensus definition of advance care planning in dementia: A 33-country Delphi study - van der Steen, Jenny T; Nakanishi, Miharu; Van den Block, Lieve; Di Giulio, Paola; Gonella, Silvia; In der Schmitten, Jürgen; Sudore, Rebecca L; Harrison Dening, Karen; Parker, Deborah; Mimica, Ninoslav; Holmerova, Iva; Larkin, Philip; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION: Existing advance care planning (ACP) definitional frameworks apply to individuals with decision-making capacity. We aimed to conceptualize ACP for dementia in terms of its definition and issues that deserve particular attention. METHODS: Delphi study with phases: (A) adaptation of a generic ACP framework by a task force of the European Association for Palliative Care (EAPC); (B) four online surveys by 107 experts from 33 countries, September 2021 to June 2022; (C) approval by the EAPC board. RESULTS: ACP in dementia was defined as a communication process adapted to the person's capacity, which includes, and is continued with, family if available. We identified pragmatic boundaries regarding participation and time (i.e., current or end-of-life care). Three interrelated issues that deserve particular attention were capacity, family, and engagement and communication. DISCUSSION: A communication and relationship-centered definitional framework of ACP in dementia evolved through international consensus supporting inclusiveness of persons with dementia and their family. HIGHLIGHTS: This article offers a consensus definitional framework of advance care planning in dementia. The definition covers all stages of capacity and includes family caregivers. Particularly important are (1) capacity, (2) family, (3) engagement, and communication. Fluctuating capacity was visualized in relation to roles and engaging stakeholders.
Keywords: palliative care; conceptualization; decision-making; Terminal Care; delfská metoda; Humans; demence; předběžné plánování péče; Consensus; Delphi Technique; Advance Care Planning; advance care planning; Dementia; dementia; lidé; konsensus; péče o umírající